Hubungan Antara Usia, Aktivitas Fisik, Pola Makan, dan Kebiasaan Merokok dengan Hipertensi pada Masyarakat Desa Plosojenar, Ponorogo - Renaningtyas Nityasani; Eny Qurniyawati; Vivin Asniyah Akasa; Nadia Rizqiyah Syafitri (Media Gizi Kesmas, 2025)
Background: Hypertension is an increasing global health concern, including particularly among adults in community settings. At this stage of life, unhealthy lifestyle habits such as low physical activity and high intake of salty or processed foods directly increase the risk of early hypertension. Objectives: This study aims to analyze the relationship of age, physical activity, diet, and smoking habits with the incidence of hypertension in Plosojenar Village, Ponorogo. Methods: This study employed an observational analytic design with a case-control method involving 154 respondents, consisting of 77 individuals with hypertension and 77 individuals in the control group. Data were collected through interviews and questionnaires, then analyzed using the chi-square test. The physical activity questionnaire included three items related to exercise, daily physical movement, and routine activities. The dietary pattern questionnaire included seven items related to high-fat foods, fried foods, fast food, instant food, salted foods, fruit intake, and coffee consumption. Results: The study showed that age above 45 years (p-value 2.2E-16, OR 71.191710) and lack of physical activity (p-value 3.8E-03, OR 15.73508) was significantly associated with hypertension. Dietary patterns also showed a significant effect (p-value 1.8E-02), although with a more moderate strength of association. In contrast, smoking habits did not show a significant relationship with the incidence of hypertension (p-value 6.2E-01). Conclusions: Age and physical activity are the main risk factors for hypertension in Plosojenar Village. Therefore, public health interventions should focus on prevention through promoting physical activity and improving diet. With 77 cases of hypertension, including one adolescent case, early prevention efforts and risk management in vulnerable groups are necessary to reduce the future prevalence of hypertension.